Relationship between knowledge of anemia and attitudes toward adherence to iron supplementation among high school students: A cross-sectional study - Anggaraini, Nova Dwi; Lestari, Dian (Indonesian Journal of Health Services, 2025)
Background: Iron deficiency anemia remains a major public health concern among adolescent girls, particularly in developing countries. Iron supplementation programs have been implemented to prevent anemia; however, adherence to iron tablet consumption among adolescents remains low despite educational efforts. Understanding behavioral determinants such as knowledge and attitudes is important for improving program effectiveness. Objective: To examine the relationship between knowledge of anemia and attitudes toward adherence to iron supplementation among female high school students. Methods: A quantitative analytic survey using a cross-sectional design was conducted from March to June 2025 at a senior high school in Ogan Komering Ulu Regency, South Sumatra, Indonesia. The study involved 57 female students selected through purposive sampling from grades X and XI. Data were collected using a validated structured questionnaire assessing knowledge about anemia, attitudes toward iron supplementation, and adherence to iron tablet consumption. Descriptive statistics were used for univariate analysis, while the Fisher Exact Test was applied to assess associations between variables due to unmet assumptions for the Pearson Chi-square test. Statistical analysis was performed using SPSS. Results: Most respondents demonstrated good knowledge about anemia (91.2%). However, adherence to iron supplementation was low, with 89.5% of respondents categorized as non-adherent. Bivariate analysis showed no significant association between knowledge and adherence to iron supplementation (p = 0.439). Similarly, no significant relationship was found between attitudes and adherence (p = 1.000). The findings indicate that adequate knowledge and attitudes alone may not be sufficient to influence adolescents’ compliance with iron supplementation programs. Conclusion: Knowledge and attitudes toward anemia were not significantly associated with adherence to iron supplementation among adolescent girls. Behavioral, environmental, and motivational factors may play a greater role in influencing adherence, suggesting that future interventions should integrate educational strategies with behavioral support mechanisms to improve program outcomes.